Transactions on edutainment V - Pan, Zhigeng; Cheok, Adrian David; Müller, Wolfgan; Yang, Xub (Lecture Notes in Computer Science, 2011)
This journal subline serves as a forum for stimulating and disseminating innovative research ideas, theories, emerging technologies, empirical investigations, state-of-the-art methods, and tools in all different genres of edutainment, such as game-based learning and serious games, interactive storytelling, virtual learning environments, VR-based education, and related fields. It covers aspects from educational and game theories, human-computer interaction, computer graphics, artificial intelligence, and systems design. The 5th volume in this series represents a selection of 12 contributions from DMDCM 2010, the 5th International Conference on Digital Media and Digital Content Management, held in Chongqing, China, in December 2010, as well as 9 regular papers. The papers cover topics such as human-computer interaction, virtual exhibit, face recognition, character animation etc.; they moreover present a large number of application examples in the area of e-learning, game, animation, multimedia, and virtual reality which gives more broad view on the application of edutainment-related techniques